Objective and Subjective Determinants of Human Estrangement in Digital Society - Odilovna, Oripova Mokhidil (International Journal of Formal Education, 2025)
This paper thoroughly explores how the human estrangement issue gains progressively critical relevance within today's digitalized society. Analysis encompasses both objective and subjective determinants of estrangement processes that materialize through digital technology advancement and information infrastructure evolution. Moreover, this investigation examines transformations within information society's social architecture, virtual interaction patterns and their influence upon human personality in Uzbek society, alongside presenting resolution pathways.